Malawi : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This paper analyzes key findings of the second progress report on Malawi's Poverty Reduction Strategy Paper (PRSP). The second progress report has focused on assessing inputs, outputs, and to some extent outcomes of the implementation of the strategy. In terms of inputs, this report analyzes expenditure by pillars, protected pro-poor activities, and functional analysis of government expenditure pattern. The outputs and outcomes analysis are presented in the report by comparing the planned activities and their targets outlined in the strategy to the actual progress and targets achieved over the second year of the implementation period.